2020
DOI: 10.1515/chem-2020-0097
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical evaluation of the fruit pulp of Opuntia spp growing in the Mediterranean area under hard climate conditions

Abstract: AbstractBarbary fig called prickly pear is a plant belonging to family Cactaceae growing under hard climate conditions. A spiny variety of prickly pear named “Drbana” (Opuntia megacantha) and two non-spiny varieties named “Akria” and “Mlez” (Opuntia ficus-indica) growing in the Rhamna region (Morocco) were studied in terms of physicochemical characteristics. The physicochemical characterization (hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Processing techniques have a direct impact on TP yield [ 20 , 63 ]. Oven dried Morocco peel TP values ranged from 1.7 to 2.4 g GA/100 g d.w depending on the variety [ 51 ]. Mexican peel and pulp fruit subjected to high hydrostatic pressure (HHP) accounted for 11 and 4 g GA/g d.w [ 64 ].…”
Section: Resultsmentioning
confidence: 99%
“…Processing techniques have a direct impact on TP yield [ 20 , 63 ]. Oven dried Morocco peel TP values ranged from 1.7 to 2.4 g GA/100 g d.w depending on the variety [ 51 ]. Mexican peel and pulp fruit subjected to high hydrostatic pressure (HHP) accounted for 11 and 4 g GA/g d.w [ 64 ].…”
Section: Resultsmentioning
confidence: 99%
“…This result was less than the results of Abdulkadir et al (2022), who found the juice percentage was 54.18 and 49.41 in red and white prickly pear fruit juice, respectively. For the agro-industrial sector, the high levels of prickly pear fruit juice increase their commercial value because the juice content is the first factor that influences the cost price (Bourhia et al, 2020). These results suggest that further investigation is necessary to understand the variables that influence the juice content of prickly pear fruit juice as well as its commercial value.…”
Section: Weight Percentage Of Fruit Fractionsmentioning
confidence: 99%
“…Based on these results, prickly pear pulp has about the same amount of ascorbic acid as both red and white cactus pear juice and purple and green cactus pear fruit. Bourhia et al (2020) reported that the Akria variety of prickly pear pulp has the highest ascorbic acid content (26.48 mg/100 g). A similar result was reported by Elshehy et al (2020) for the ascorbic acid content in prickly pear fruit juice from Egypt (26.76 mg/100 g).…”
Section: Ascorbic Acidmentioning
confidence: 99%
“…The Brix/Acidity ratio is an essential indicator for determining the taste and quality of fruit. It is also used to determine fruit ripeness (Bourhia et al, 2020). Orange pulp exhibited the highest ºBrix/acidity ratio with 12.58 ± 0.90 (Table I).…”
Section: Total Titratable Acidity and ºBrix/acidity Ratiomentioning
confidence: 99%